23. STUDY ON THE STATUS OF PERIPHERAL VENOUS PHLEBITIS AND RELATED FACTORS IN CANCER PATIENTS RECEIVING CHEMOTHERAPY AT DA NANG ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Background: Cancer and chemotherapy could cause changes in the blood, leading to damage to the vascular endothelium, increasing the likelihood of peripheral vein inflammation. Objective: To assess the status of peripheral vein inflammation and identify some related factors in cancer patients undergoing chemotherapy at Da Nang Oncology Hospital. Study Period: From October 2024 to February 2025 at the Internal Medicine Department 1, Da Nang Oncology Hospital.Methods: A cross-sectional study of 220 cancer patients receiving chemotherapy via peripheral venous catheter.Results: The incidence of peripheral vein inflammation was 18.6%, with grade 1: 70.7% of cases, grade 2: 29.3%. No cases of grades 3, 4, 5. There was a correlation with age, catheter insertion site, and the number of reinsertions of the catheter.Conclusion: Cancer patients receiving chemotherapy via peripheral venous catheter are at high risk for peripheral venous inflammation.
Keywords: Peripheral vein inflammation; cancer; chemotherapy; Da Nang Oncology Hospital